Analisis resiko kesehatan lingkungan pencemaran timbal (Pb) pada hasil laut yang beredar di pasar Sambu Medan - Tina Meirindany; Khodijah Tussolihin Dalimunthe (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Plumbum (Pb) is a heavy metal that damages and pollutes the environment. The presence of these heavy metal damages and pollutes the environment. The presence of these heavy metals changes marine biota's life and threatens human health through contaminated food chains. The results of measuring lead (Pb) levels in anchovies and squid circulating in the Sambu Market in Medan exceed the 2009 SNI threshold. This study aims to estimate the exposure to lead (Pb) of those who eat anchovies and squid in the Sambu Market with Desktop Risk Analysis of Environmental Health. The research results show that the risk magnitude (RQ) of exposure to Plumbum (Pb) in people who consume anchovies and squid is RQ>1. Based on risk management, the safe consumption rate is at least 0.06 grams per day for adults with a body mass of 55 kg. Risk management is also carried out by managing sources of reciprocal pollutants (Pb) by controlling the amount of industrial waste that may be discharged into waters, which requires direct supervision from the local Environmental Service.